Expression Profiles of Vpx/Vpr Proteins Are Co-related with the Primate Lentiviral Lineage - Sakai, Yosuke; Miyake, Ariko; Doi, Naoya; Sasada, Hikari; Miyazaki, Yasuyuki; Adachi, Akio; Nomaguchi, Masako (Frontiers in Microbiology, 2016)
Viruses of human immunodeficiency virus type 2 (HIV-2) and some simian immunodeficiency virus (SIV) lineages carry a unique accessory protein called Vpx. Vpx is essential or critical for viral replication in natural target cells such as macrophages and T lymphocytes. We have previously shown that a poly-proline motif (PPM) located at the C-terminal region of Vpx is required for its efficient expression in two strains of HIV-2 and SIVmac, and that the Vpx expression levels of the two clones are significantly different. Notably, the PPM sequence is conserved and confined to Vpx and Vpr proteins derived from certain lineages of HIV-2/SIVs. In this study, Vpx/Vpr proteins from diverse primate lentiviral lineages were experimentally and phylogenetically analyzed to obtain the general expression picture in cells. While both the level and PPM-dependency of Vpx/Vpr expression in transfected cells varied among viral strains, each viral group, based on Vpx/Vpr amino acid sequences, was found to exhibit a characteristic expression profile. Moreover, phylogenetic tree analyses on Gag and Vpx/Vpr proteins gave essentially the same results. Taken together, our study described here suggests that each primate lentiviral lineage may have developed a unique expression pattern of Vpx/Vpr proteins for adaptation to its hostile cellular and species environments in the process of viral evolution.